Pengaruh Kepuasan Kerja terhadap Disiplin Kerja Perekam Medis Informasi Kesehatan (PMIK) di Wilayah DPD PORMIKI DKI Jakarta - Nanda Dina Cahya; Husni Abdul Muchlis; Hosizah Hosizah; Nauri Anggita Temesvari (Pusat Riset dan Inovasi Nasional, 2025)
Problems related to work discipline among Medical and Health Information Recorders (PMIK) observed during fieldwork practice in hospitals include non-compliance with punctuality, delays in completing tasks, and ineffective use of break time. These conditions indicate that the level of work discipline among PMIK personnel is suboptimal, which may affect productivity and service quality. Job satisfaction is one of the factors presumed to influence work discipline. This study aimed to examine the effect of job satisfaction on work discipline among PMIK members within the DPD PORMIKI DKI Jakarta area. A quantitative approach with a cross-sectional design was employed. Using a quota sampling technique, 94 respondents were selected from a total population of 1,490. The results showed that job satisfaction had a positive and significant effect on work discipline (p-value = 0.000). The regression equation obtained was Y = 5.288 + 0.606X. Job satisfaction accounted for 75.1% of the variance in work discipline, while the remaining 24.9% was influenced by other factors not examined in this study. Therefore, efforts to enhance job satisfaction are essential to improve work discipline among PMIK professionals.